Performing weeds: Gardening, plant agencies and urban plant conservation - Doody, B; Perkins, H; Sullivan, J; Meurk, C; Stewart, G (Elsevier, 2014)
Private domestic gardens have been the site of diverse inquiry in both the social and natural sciences. Intersected by these inquiries this paper focuses on how ‘weeds’ are (re)constituted through gardening practices in domestic gardens in Christchurch, New Zealand. The paper arises out of an interdisciplinary ecological and social scientific study of the factors influencing the distribution and regeneration of 12 bird-dispersed native woody species from Riccarton Bush, an urban forest remnant of significant ecological rarity, into surrounding residential properties. As part of this study we were especially interested in how people’s everyday experiences and encounters in their gardens guide their gardening practices and what possibilities, if any, these create for self-introduced native seedlings to establish, and mature into adults. Drawing inspiration from literatures on human–plant relations we use the concepts of performance, non-human and ‘planty’ agencies to argue that weeds are performed by people and plants rather than having a pre-determined or pre-figured meaning. Empirically the paper seeks to highlight the diverse, unique and disruptive agencies of plants. Methodologically it reflects on ways of engaging with and researching human–plant relations. In concluding, the paper examines how concepts of performance, non-human and planty agencies can provide insights for weed management and urban plant conservation.